Slope Conservation and Landslide Disaster Mitigation through the TANGKAS Program based on Community Participation in Jambeyan Village - Prihandi, Singgih; Rahmat Runjung, Benyamin Ricky; Yuliana, Hesti; Melani, Karisma Dwi; Safitri, Kartika Dewi; Saputri, Maharani Bintang; Saharani, Nariswari Putri; Az Zahra, Nazwah Ummu; Inayah, Nurul Fitri; Katamsa, Risam; Dhanoko, Thorriqul Astyo (Society : Jurnal Pengabdian Masyarakat, 2025)
Jambeyan Village in Sambirejo Sub-district, Sragen Regency, is a region highly prone to landslides, especially in slope areas that have not been optimally managed. This community service program aims to raise awareness and encourage community participation in slope conservation and landslide disaster mitigation through the TANGKAS program (Tanggap Longsor Berbasis Aksi Masyarakat or Community-Based Landslide Response). The methods applied include socialization, evacuation planning workshops, installation of evacuation route signs, and participatory soil conservation education. The results show an increase in community understanding of landslide risks and disaster preparedness, as evidenced by active participation in evacuation simulations and the maintenance of protective slope vegetation. The TANGKAS program has proven effective in fostering local resilience and enhancing collaboration among villagers, local authorities, and external stakeholders in disaster risk reduction efforts.